Identification of key somatic features that are common and the ones that differ between swim strokes through allometric modeling - Rejman, Marek; Nevill, Alan M.; Garrido, Nuno D.; Rudnik, Daria; Morais, Jorge E. (Frontiers in Sports and Active Living, 2023)
Introduction The aim of this study was to explore which key somatic features are common to four swim strokes and medley, and specifically to identify which characteristics benefit only specific strokes. Methods The sample was composed of 130 swimmers (95 males aged 19.5 ± 2.9 years and 35 females aged 18.4 ± 2.8 years). A set of anthropometric variables was used to predict swimming speed in the four swimming strokes and medley. Results A multiplicative model with allometric body size components was used to identify the demographic and anthropometric predictors of swimming speed. Trunk height and waist circumference were the only variables significantly different among swimming strokes (p < 0.05). Associations between swimming speed and arm length were similar in breaststroke and medley, and in freestyle, backstroke and butterfly (R2 = 60.9%). The model retained as swimming speed predictors the age2, upper body circumference, hand breadth, waist circumference, and subscapular skinfold thickness (these last two had negative associations). Conclusion All these predictors were common to all four swim strokes and medley. Arm length was also retained as a significant predictor, but this one varied significantly between the four different swim strokes and medley. These findings highlight the importance of having a “V-shape” trunk, longer upper limbs, and large hands as predictors of swimming performance.